2001
DOI: 10.2337/diabetes.50.2007.s52
|View full text |Cite
|
Sign up to set email alerts
|

Role of pancreatic beta-cells in the process of beta-cell death.

Abstract: Studies on the pathogenesis of type 1 diabetes have mainly focused on the role of the immune system in the destruction of pancreatic beta-cells. Lack of data on the cellular and molecular events at the beta-cell level is caused by the inaccessibility of these cells during development of the disease. Indirect information has been collected from isolated rodent and human islet cell preparations that were exposed to cytotoxic conditions. This article reviews in vitro experiments that investigated the role of beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 32 publications
(69 reference statements)
5
44
0
Order By: Relevance
“…We examined whether isolated postnatal human duct-cell preparations have this property when transplanted under the kidney capsule of normal mice. A duct cell-containing fraction was obtained during the islet-cell isolation procedure that is conducted for our clinical trial on beta-cell transplantation, and is further enriched during suspension culture [19,20,21,22,23]. Grafts are then prepared that contain approximately 0.5 million cells and mainly consist of CK 19 marked duct cells (80%) with acinar cells as major contaminant (18%); endocrine and insulin-positive cells were rare (<2%) but consistently present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined whether isolated postnatal human duct-cell preparations have this property when transplanted under the kidney capsule of normal mice. A duct cell-containing fraction was obtained during the islet-cell isolation procedure that is conducted for our clinical trial on beta-cell transplantation, and is further enriched during suspension culture [19,20,21,22,23]. Grafts are then prepared that contain approximately 0.5 million cells and mainly consist of CK 19 marked duct cells (80%) with acinar cells as major contaminant (18%); endocrine and insulin-positive cells were rare (<2%) but consistently present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that addition of an extracellular matrix and selected agents might induce differentiation of duct cells to islet cells [18]. It is important to know whether a similar process can occur in human islet grafts which are known to be heavily contaminated by pancreatic duct cells [19,20,21]. To investigate this possibility we prepared human pancreatic duct cells [22,23] and followed their cellular composition and cell population volumes over 10 weeks after transplantation in nude mice.…”
mentioning
confidence: 99%
“…Clearly, other factors are playing a role. These could include noxious products of the beta cells themselves [43] or lack of positive/protective factors normally contributed by the non-beta cells of human isolated islets. These must now be addressed in further studies and appropriate intervention conceived to block entirely cell death and restore glucose-sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that Ucp2-KO macrophages have increased MAPK activation in response to LPS and therefore produce more NO (8). NO and IL-1␤ are two important mediators in inflammation and ␤-cell death (20,21). To investigate whether MLDS treatment differentially affected macrophage activity in Ucp2-KO and Ucp2-WT mice, peritoneal macrophages were isolated from both types of mice.…”
Section: Increased No and Cytokine Production Of Macrophages From Mlds-mentioning
confidence: 99%